Gastric Pouch Gastrointestinal Stromal Tumour Post-Roux-en-Y Gastric Bypass: A First Reported Case - Wissam Dib; Melissa Kyriakos Saad; Georges El Hachem; Bassim Sawan; Elias Saikaly (European Medical Journal)
Gastric gastrointestinal stromal tumour is an extremely rare condition to occur after bariatric surgery. To the authors’ knowledge, only two cases of gastric gastrointestinal stromal tumours after Roux-en-Y gastric bypass have been reported in the medical literature, both occurring in the excluded gastric remnant. Herein, the authors report the third case of gastric gastrointestinal stromal tumour post-Roux-en-Y gastric bypass, and the first case to occur in the gastric pouch, which was managed surgically by laparoscopic resection. From here, combining the observations of clinicians treating and following up patients post-bariatric surgery in an international database will be beneficial to patients, and aid in development of surveillance guidelines.